PERAN GURU SEBAGAI PEMBIMBING UNTUK MEMBANTU PERKEMBANGAN ANAK USIA DINI DI PAUD AISYIYAH BUSTANUL ATFHAL KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Isdalia, Nila; Syarif, Mellyarti; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
The background of this research is teacher role as guide to help student development in PAUD Aisyiyah Bustanul Atfhal. Teacher as guide have role to give counseling to students, this way to help student playing progress serve oneâs purpose. The research focus is: (1) Teacher role as guide to studentâs cognitive progress, (2) Teacher role as guide to studentâs social progress, (3) Teacher role as guide to studentâs emotion progress. This research is descriptive qualitative, informants in this research were teacher in PAUD Aisyiyah Bustanul Atfhal sub district Sutera, Pesisir SelatanÂ as many as four people and head master and studentâs parents in PAUD Aisyiyah Bustanul Atfhal as supporting informants. Data were collected by interview and documentation. Result of this research show the teacher role as guide to help studentsâ cognitive progress, social progress, and emotion progress in PAUD, it can see that students have ability to learning recapitulation and filter, behavior and interaction, expression the feeling.